The Uptake of 32P by Brown Planthoppers (Nilaparvata Lugens Stal) Gonads - S. Sastrodihardjo; R.A. Wahid (Journal of Mathematical and Fundamental Sciences, 1980)
Abstract. The radioisotop 32P has been used quite extensively in the field of insect ecology and insect physiology. It has been widely known that 32P is one of the several isotopes applied to tag the insects for migration studies, to estimate the sap uptake or the excretion of sucking insects as well as for the study of sperms transfer in sterilization study. Within the scope of Sterile Insects Techniques, the study on the uptake of 32P by the gonads of brown planthoppers (Nilaparvata lugens Stal) could be meaningful. The 32P radioisotopes used had been one of most available products of the Centre. The radioisotope provided also a possible source for sterilization due to its accumulative effect. Results of the investigation on the 32P uptake by the whole body and gonads after feeding on radioactive rice seedlings will be reported.a. Absorption of 32PP by rice seedling ( Pelita I/1 )The specific activities of 32PP (Carrier free) applied to the two week old seedlings were 1, 2, 4, 6, 8, 10, 15, and 20 uci/cc. The radioactivity count of hoppers and leaf tips were made 48 hrs. after submersion of the seedlings in the radioactive solution.b. Absorption of 32PP by BPHThe radioactive seedlings were offered to BPH after being washed thoroughly with water. A single BPH is fed on a single rice seedlings kept in a glass tube. Count of the whole body and dissected gonads were made 24, 48, 72, and 96 hours after feeding. Sterility effects were observed from the mating of 32P treated hoppers. Sari. Radioisotop 32p telah dipergunakan secara luas dalam bidang ekologi dan fisiologi serangga. Telah diketahui secara luas bahwa 32Pp merupakan salah satu dari beberapa isotop yang telah dipergunakan untuk penandaan serangga guna menunjang studi migrasi, pengambilan cairan tanaman ataupun ekskresi dari serangga penghisap ataupun studi tentang transfer dari sperma. Didalam ruangan lingkup Teknik Serangga Mandul, studi dari pengambilan 32p oleh gonad dari wereng coklat (Nilaparvata lugens Stal) dapat mempunyai arti penting mengingat bahwa produk ini merupakan salah satu hasil yang mudah diperoleh dari PPTN dan mempunyai prospek yang baik sebagai sumber sterilisasi internat mengingat pengaruh akumulatipnya. Berikut adalah hasil penelitian tentang pengambilan 32P oleh seluruh tubuh dan gonad wereng setelah diberi makan benih padi yang radioaktip.a. Absorbsi 32P oleh benih padi (Pelita I/1)Aktivitas jenis dari 32P (bebas pengemban) yang dipergunakan untuk penandaan benih padi berumur 2 minggu adalah 1,2,4,6,8,10,15 dan 20 uci/cc. pencacahan terhadap ujung daun dan wereng dilakukan setelah akar benih padi direndam dalam larutan radioaktip selama 48 jam.b. Absorbsi 32P oleh wereng coklatBenih padi yang telah radioaktip dumpankan kepada wereng coklat setelah dicuci bersih dengan air suling.Satu wereng coklat dewasa diberi makan satu benih padi di dalam sebuah tabung kaca. Pencacahan dari tubuh dan gonad wereng yang telah dikeluarkan dilakukan 24, 48, 72, dan 96 jam setelah makan. Efek pemandulan diamati dari perkawinan wereng yang telah mendapat perlakuan 32P.